Pengoptimalan Tenaga Kerja Dan Penentuan Waktu Standar Pada Produksi Songkok (Studi Kasus di Home Industry Achmad Rochman Lamongan) - Muhammad Subhan Afifi; Istantyo Yuwono (Fakultas Teknik Universitas Tulang Bawang, 2023)
Home Industry Achmad Rochman is a company engaged in the manufacture of skullcaps, in the production of skullcaps there are 3 types namely AC skullcaps, Standard skullcaps and stacking skullcaps, in the production process the company does not yet have a standard time as a reference for making skullcap products. The production process at Achmad Rochman is only based on targets so that workers must complete according to the company's targets because they do not yet have a standard time reference for each skullcap and an order system within the company, namely Make to order and requests are always changing. The results of calculating the standard time using the working time measurement method with a stop clock yield a standard skull cap of 1099.33 seconds, an AC skullcap has a standard time of 1189.13 seconds and for stacking skullcaps a standard time of 1129.29 seconds. Optimizing the workforce using the Work load Analysis (WLA) method and producing a standard skull cap requires 20 workers, corporate stacking requires an optimal workforce of 20 workers and AC cap to meet demand requires an optimal workforce of 30 workers plus 2 workers in sewing operations sum Keyword: Cycle Time, Work Load Analysis, Work Sampling.